STRATEGIC PLANNING AND CREATIVITY SKILLS AS PREDICTORS OF SMES PERFORMANCE (NAU Journal of Technology and Vocational Education, 2025)
The study examined strategic planning and creativity skills as predictors for SMEs performance. Four research questions guided the study. A descriptive research design of survey was used. The population of this study comprised all SMEs in Sagamu and Ijebu-Ode local government areas of Ogun State, Nigeria.  A total of 80 SMEs were selected as sample size of the study. Multistage sampling technique was used for selecting sample. After that, purposive sampling technique was adopted in selecting the sample size of the sample. Researcher developed instrument tagged: Strategic Planning, Creativity Skills and SMEs Performance Questionnaire (SPCSSMESPQ) was used for data collection with reliability 0.92. Research questions 1 and 2 were analysis using mean and standard deviation. Research questions 3 and 4 answered using Pearson Product Moment Correlation (PPMC). The findings of the study revealed that capability to develop a business concept, effective decision making, innovative business ideas, novel business products and services, and inspirational skills were among creativity skills needed for SMEs performance. Business review, marketing and sales plans, effective collaboration between people – leadership, training and development, operations – premises, production, it and financials – cash flow, requirements for finance, planned investments were among the level are strategic planning needed for SMEs performance. There was relationship between strategic planning and SMEs performance (r = 0.495, p < .05). There was positive relationship between creativity skills and SMEs performance (r = 0.557, p < .05). It was recommended, among others, that government through its agencies should endeavour to organize capacity building workshop for managers from time to time in order to understand the salient roles and impacts of strategic planning and creativity skills on SMEs performance.
Keywords: Strategic planning; creativity skills; SMEs Performance